Feasibility of primary anastomosis for right-sided colonic atresia: A case report - Suhaimi, Muhammad Shamil; Othman, Mohd Yusran; Kamilen, Khalilah Alhuda (Journal of Neonatal Surgery, 2021)
Background: Colonic atresia (CA) is a rare cause of congenital intestinal obstruction. The management of CA is challenging because of its rarity. Case Presentation: We present a case of right-sided CA in a term male baby weighing 3006 gm, without any other comorbidity. Type 1 atresia was seen at ascending colon and upon decompression, a reasonable caliber was achieved for a primary anastomosis following distal Cheatle slit and proximal tapering. Postoperative recovery was uneventful. Conclusion: Primary anastomosis is a feasible option in right-sided CA when no major comorbidity is present and a normal distal colon with reasonable caliber is certain.